Aldosterone Synthase Promoter Polymorphism and Cardiovascular Phenotypes in a Large, Multiethnic Population-Based Study. Issue 7 (October 2015) - Byrd, James Brian; Auchus, Richard J.; White, Perrin C.
Background: A single-nucleotide polymorphism in the aldosterone synthase gene (CYP11B2) promoter [−344C/T, rs1799998] has been reported to associate with cardiovascular phenotypes. Methods: The Dallas Heart Study is a large, multiethnic cohort with a high prevalence of hypertension. We genotyped 3452 Dallas Heart Study participants for −344C/T. Generalized linear models were used to assess whether variation at −344C/T associated with plasma aldosterone concentration (PAC), systolic and diastolic blood pressure (SBP and DBP), plasma glucose (in persons with no diabetes), HOMA IR (Homeostasis Model Assessment as an Index of Insulin Resistance), and left ventricular (LV) mass indexed to height. Systolic blood pressure and DBP were significantly higher in blacks compared with whites ( P < 0.001 for SBP and for DBP) and Hispanics ( P < 0.001 for SBP and for DBP). Log-transformed body mass index was also significantly higher in blacks compared with whites ( P < 0.001), but not Hispanics ( P = 0.10). Log-transformed PAC was higher in whites compared with blacks ( P < 0.001), but did not differ significantly in whites compared with Hispanics ( P = 0.73). In univariate and multivariable analysis, −344C/T was not significantly associated with PAC within any ethnicity. In univariate and multivariable analysis, −344C/T was not associated with SBP or DBP within any ethnicity. After adjustment for multiple testing, univariate and multivariable analyses revealed no association between −344C/T and plasma glucose in patients with no diabetes, HOMA IR, or LV mass indexed to height. Conclusions: We were unable to reproduce previously reported associations between −344C/T and PAC, blood pressure, plasma glucose, or LV mass. Methodological differences might explain the differences between our findings and those previously reported.